Aquifer Simulation Model in Tioman Island (Malaysian Journal of Civil Engineering, 2018)
Tioman Island which is situated in the southeast of Pahang State is one of smallislands in Malaysia that has been promoted as a tourism destination. Based onprevious study, the island requires more than 2000 m'/day of water for domesticand tourism industry consumption, and the demand is expected to rise due to theincreases in population and tourism activities. Study on groundwater of Tekekaquifer indicates a good potential for water resource to meet the demand of thefuture water-needs in Tioman Island. An intensive study is being carried out toinvestigate the quantity of water resources in the island. For predicting the amountof groundwater potential that can be extracted, ASM (Aquifer Simulation Model)is used. The paper present the finding of the amount of the groundwater potentialthat can be extracted in Tekek, Tioman Island.